Designing an ESP reading syllabus for the second-year students of Business Administration at the Waterway Transport Vocational College Number 1 - Nguyen, Thi Thanh Ha (ĐHNN, 2017)
The purpose of this thesis is to design an ESP reading syllabus for the second-year students of business administration at the Waterway Transport Vocational College Number 1. It is hoped that the syllabus will benefit the students, teachers in teaching and (...)